Infertile Women with Bilateral Obstructed Tubes: (A presentation of 7 cases) - Osman Develioğlu; Eser Özyürek; Yurtkuran Sadıkoğlu; Ganime Sadıkoğlu; Ercan Tuncel (Medical Network, 2006)
OBJECTIVE: Selective salpingography (SS), and tubal cannulation (TC), are possible alternatives to IVF(ICSI)-ET treatment f or bilateral proximal tubal occlusion . We present a series of infertile patients who presented with bilateral tubal blockage in their hysterosalpingographies (HSG's); and were treated with selective salpingography and tubal cannulation. STUDY DESIGN: Case presentation of 7 infertile patients with bilateral proximal tubal obstruction who were treated with SS and if required TC to provide tubal patency and followed-up for 3 years. RESULTS: In 6 of the 7 couples, at least one of the fallopian tubes was opened with SS-TC. At the end of 3 years'f ollow-up of these couples, 4 achieved pregnancy; 2 being spontaneously and 2 with conventional infertility treatment. 2 of these pregnant couples ( both conceiv ed spontaneously) had diminished ovarian reserves, as well. CONCLUSION: SS-TC is an important, effective and a rather neglected potential alternative to assisted reproductive technologies which demands to be studied in randomized controlled trials.